Pemahaman terhadap Petani Kecil sebagai Landasan Kebijakan Pembangunan Pertanian - nFN Syahyuti (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2013)
EnglishImproving the farmers’ welfare is one of goals in agricultural development policy. Inadequate government’s concern to farmers is observed from the definition of farmers in various regulations and understanding of small farmers’ existence, role and characters. Lacks of understanding and taking side to small farmers are indicated by absence of using the term of